The unknown Hsüan-tsang - Devahuti, D. (New Delhi ; New York : Oxford University Press, 2001)
Biographical account of Xuanzang, ca. 596-664, a Chinese Buddhist monk who visited India in the seventh century A.D.
Includes bibliographical references (p. [168]-170) and index.
Keywords: Xuanzang, -- approximately 596-664.; Buddhist priests -- China -- Biography